Individual difficulties and resources: a qualitative analysis in patients with advanced lung cancer and their relatives - Sparla, Anika; Villalobos Bollen, Matthias Americo; Krug, Katja; Kamradt, Martina; Coulibaly, Kadiatou; Szecsenyi, Joachim; Thomas, Michael; Gusset-Bährer, Sinikka; Ose, Dominik; Flach-Vorgang, Sebastian (Patient preference and adherence, 2016)
Purpose: Lung cancer is a disease with a high percentage of patients diagnosed in an advanced stage. In a situation of palliative treatment, both patients and their relatives experience diverse types of distress and burden. Little research has been done to identify the individual difficulties and resources for patients with advanced lung cancer and their relatives. Especially, standardized questionnaire-based exploration may not assess the specific distressing issues that pertain to each individual on a personal level. The purpose of this qualitative study is to explore and compare individual difficulties and resources for lung cancer patients and their relatives within the palliative care context.Methods: Data were collected by qualitative interviews. A total of 18 participants, nine patients diagnosed with advanced lung cancer (International Classification of Diseases, tenth edition, diagnosis C-34, stage IV) starting or receiving palliative treatment and nine relatives, were interviewed. Data were interpreted through qualitative content analysis.Results: We identified four main categories of difficulties: communication and conflicts, home and everyday life, thinking about cancer, and treatment trajectory. In general, difficulties were related to interpersonal relationships as well as to impact of chemotherapy. Family, professional caregivers, and social life were significant resources and offered support to both patients and relatives.Conclusion: Results suggest that patient and relative education could reduce difficulties in several areas. Patients seem to struggle with the fear of not having any perspective in therapy. Relatives seem to experience helplessness regarding their partner’s deterioration and have to handle their own life and the care work simultaneously. The most important resource for both patients and relatives is their family. In addition, professional lung cancer nurses support relatives in an emotional and organizational way. Intense supportive care for relatives should be standardized. Keywords: inoperable lung cancer, palliative care, difficulties, resources, health services research, qualitative research